γ-Secretase Inhibitor, DAPT Inhibits Self-renewal and Stemness Maintenance of Ovarian Cancer Stem-like Cells In Vitro - Jiang, Li-yu (Springer-Verlag Berlin Heidelberg, 2011)
OBJECTIVE: The Notch signaling pathway plays an important role in the stem cell signaling network and contributes to tumorigenesis. However, the functions of Notch signaling in ovarian cancer stem cells (OCSCs) are not well understood. We aimed to investigate the effects of Notch blockade on self-renewal and stemness maintenance of OCSCs. METHODS: Ovarian cancer stem-like cells were enriched from ovarian cancer cell lines in serum-free medium. A γ-secretase inhibitor, (DAPT), was used to block Notch signaling. MTT assays were performed to assess self-renewal and proliferation inhibition, flow cytometry was performed to analyze cell surface marker and immunofluorescence, Western Blot and Real-time RT-PCR assays were performed to detect Oct4 and Sox2 protein and mRNA expression of the Ovarian cancer stem-like cells treated with DAPT. RESULTS: Notch blockade markedly inhibits self-renewal and proliferation of ovarian cancer stem-like cells, significantly downregulates the expression of OCSCs-specific surface markers, and reduces protein and mRNA expression of Oct4 and Sox2 in OCSC-like cells. CONCLUSION: Our results suggest that Notch signaling is not only critical for the self-renewal and proliferation of OCSCs, but also for the stemness maintenance of OCSCs. The γ-secretase inhibitor is a promising treatment targeting OCSCs.